Authentic Assessment based on Teaching and Learning Trajectory: A Conceptual Model for Sustainable Assessment in Natural Science Learning - Mursalin, Enggal; Rochman, Chaerul; Rahmawan, Setia; Al Mufida, Asita; Ilhami, Aldeva; Aondolumun Ayua, Geoffrey; Mileniati, Fajriati Ramadhini Nur (Indonesian Journal of Science and Education, 2025)
The transformation of 21st-century education requires assessment systems that not only measure cognitive achievement but also foster deep and meaningful learning. Current practices, however, remain dominated by summative tests that emphasize memorization and fail to capture students’ holistic development. To address this gap, this article introduces the Authentic Assessment Based on Teaching and Learning Trajectory (AABTLT) as a conceptual model for sustainable assessment integrated into the learning process. AABTLT aligns learning objectives, instructional activities, and authentic assessment along structured learning trajectories, enabling teachers to monitor students’ progressive development through contextual and formative feedback. Developed through a comprehensive literature review and synthesis of studies on authentic assessment, learning trajectories, and deep learning, this model highlights the importance of assessment as a driver of learning rather than a terminal evaluation tool. The novelty of AABTLT lies in its integrative approach, combining authentic tasks, developmental indicators, and reflective practices to strengthen student engagement, critical thinking, and creativity. Its practical implications include clear guidelines for designing assessment instruments aligned with 21st-century skills and strategies for supporting teachers in formative evaluation. Future empirical research is recommended to validate the effectiveness of AABTLT in science education and interdisciplinary contexts.